2023
DOI: 10.3390/nu15204489
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Postprandial Exercise in Mitigating Glycemic Responses in Overweight Individuals and Individuals with Obesity and Type 2 Diabetes—A Systematic Review and Meta-Analysis

Jie Kang,
Brian M. Fardman,
Nicholas A. Ratamess
et al.

Abstract: Studies investigating the acute effect of postprandial exercise (PPE) on glucose responses exhibit significant heterogeneity in terms of participant demographic, exercise protocol, and exercise timing post-meal. As such, this study aimed to further analyze the existing literature on the impact of PPE on glycemic control in overweight individuals and individuals with obesity and type 2 diabetes (T2DM). A literature search was conducted through databases such as PubMed, CINAHL, and Google Scholar. Thirty-one ori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…With regards to the time window for postprandial exercise, it has been suggested that exercising too early after the meal may initially lower glucose levels, but could lead to a rebound increase later, diminishing the beneficial effects [ 12 ]. Therefore, it has been proposed that exercising in the so-called mid-postprandial period may represent the optimal choice for improving both the immediate post-meal glucose peak and overall daily glucose management in individuals with T2D or insulin resistance [ 43 ].…”
Section: Is There An Optimal Time For Exercise Relative To Meals? The...mentioning
confidence: 99%
See 1 more Smart Citation
“…With regards to the time window for postprandial exercise, it has been suggested that exercising too early after the meal may initially lower glucose levels, but could lead to a rebound increase later, diminishing the beneficial effects [ 12 ]. Therefore, it has been proposed that exercising in the so-called mid-postprandial period may represent the optimal choice for improving both the immediate post-meal glucose peak and overall daily glucose management in individuals with T2D or insulin resistance [ 43 ].…”
Section: Is There An Optimal Time For Exercise Relative To Meals? The...mentioning
confidence: 99%
“…Additionally, high-intensity exercise, due to the adrenergic response, may increase the rate of glucose appearance, resulting in the undesirable effect of blood glucose levels rising [12,42]. However, it has been previously shown that high-intensity interval exercise may increase glucose tolerance and insulin sensitivity, resulting in an enhanced glucose disposal to skeletal muscles, especially when performed after meals [43]. Therefore, the picture emerging from the current knowledge emphasizes the need to tailor exercise prescriptions to individual preferences and requirements.…”
Section: What Should Be the Exercise Duration And Intensity?mentioning
confidence: 99%